Comentarios sobre el entorno empresarial: la variable política - Silva Vegas, Gerardo (Universidad ESAN. ESAN Ediciones, 1992)
It aims to provide the manager, in his capacity as the leader of an organization that produces goods or services for society, an analytical instrument that allows him to decompose the most complex external factor: the political variable, understood as power relations, the interaction of social groups with different or antagonistic interests, and decision-making by socially powerful subjects that affects the whole. To approach the compression of this variable, an analytical instrument is proposed which combines four dimensions: contradiction between capital and labor, contradiction between State and civil society, contradiction between violence and peace and national contradiction (between protectionism and globalization or between nationalism and internationalism). Other dimensions are conceivable; however, what is important is the usefulness of the analytical method for the stated purposes. The analysis of the political variable will allow the company’s adequate understanding and, consequently, the possibility of predicting its behavior and anticipating the events.

Pretende proporcionar al directivo, en su calidad de líder de una organización productora de bienes o servicios para la sociedad, un instrumento analítico que le permita descomponer el factor externo más complejo: la variable política, entendida como relaciones de poder, la interacción de grupos sociales con intereses diferentes o antagónicos, y toma de decisiones por parte de sujetos socialmente poderosos que afectan al conjunto. Para abordar la compresión de esta variable, se propone un instrumento analítico que combina cuatro dimensiones: contradicción entre capital y trabajo, contradicción entre Estado y sociedad civil, contradicción entre violencia y paz y contradicción nacional (entre proteccionismo y globalización o entre nacionalismo e internacionalismo). Son concebibles otras dimensiones; sin embargo, lo importante es la utilidad del método analítico para los fines indicados. El análisis de la variable política permitirá a la empresa una adecuada comprensión y, en consecuencia, la posibilidad de predecir su comportamiento y anticiparse a los acontecimientos.
Keywords: External variables; Analytical method; Variables externas; Political analysis; Método analítico; Análisis político; Business strategy; Estrategia empresarial; https://purl.org/pe-repo/ocde/ford#5.02.04